SARS-CoV-2 induces human plasmacytoid predendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (J Exp Med, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here we have isolated primary SARS-CoV-2 viral strains and studied their interaction with human plasmacytoid predendritic cells (pDCs), a key player in antiviral immunity. We show that pDCs are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.
Keywords: Biomarkers; Cell Plasticity; COVID-19; Cytokines; Dendritic Cells; Host-Pathogen Interactions; Humans; Hydroxychloroquine; Immunomodulation; Immunophenotyping; Inflammation Mediators; Interferon Type I; Interferons; Interleukin-1 Receptor-Associated Kinases; Membrane Transport Proteins; SARS-CoV-2

SARS-CoV-2 induces human plasmacytoid pre-dendritic cell diversification via UNC93B and IRAK4. - Onodi, Fanny; Bonnet-Madin, Lucie; Meertens, Laurent; Karpf, Léa; Poirot, Justine; Zhang, Shen-Ying; Picard, Capucine; Puel, Anne; Jouanguy, Emmanuelle; Zhang, Qian; Le Goff, Jérôme; Molina, Jean-Michel; et al. (bioRxiv, 2021)
Several studies have analyzed antiviral immune pathways in late-stage severe COVID-19. However, the initial steps of SARS-CoV-2 antiviral immunity are poorly understood. Here, we have isolated primary SARS-CoV-2 viral strains, and studied their interaction with human plasmacytoid pre-dendritic cells (pDC), a key player in antiviral immunity. We show that pDC are not productively infected by SARS-CoV-2. However, they efficiently diversified into activated P1-, P2-, and P3-pDC effector subsets in response to viral stimulation. They expressed CD80, CD86, CCR7, and OX40 ligand at levels similar to influenza virus-induced activation. They rapidly produced high levels of interferon-α, interferon-λ1, IL-6, IP-10, and IL-8. All major aspects of SARS-CoV-2-induced pDC activation were inhibited by hydroxychloroquine. Mechanistically, SARS-CoV-2-induced pDC activation critically depended on IRAK4 and UNC93B1, as established using pDC from genetically deficient patients. Overall, our data indicate that human pDC are efficiently activated by SARS-CoV-2 particles and may thus contribute to type I IFN-dependent immunity against SARS-CoV-2 infection.